Novel 9, 9′‐(1, 3‐phenylene)bis‐9H‐carbazole‐containing copolymers as hole‐transporting and host materials for blue phosphorescent polymer light‐emitting diodes. Issue 5 (17th December 2013) - Yoon, Seung Hee; Shin, Jicheol; Um, Hyun Ah; Lee, Tae Wan; Cho, Min Ju; Kim, Yong Jae; Son, Young Hoon; Yang, Joong Hwan; Chae, Geesung; Kwon, Jang Hyuk; Choi, Dong Hoon
ABSTRACT Novel photo‐crosslinkable hole‐transport and host materials incorporated into multilayer blue phosphorescent polymer light‐emitting diodes (Ph‐PLEDs) were demonstrated in this study. The oxetane‐containing copolymers, which function as hole‐transport layers (HTL), could be cured by UV irradiation in the presence of a cationic photoinitiator. The composition of the two monomers was varied to yield three different hole‐transporting copolymers, [Poly(9, 9′‐(5‐(((4‐(7‐(4‐(((3‐methyloxetan‐3‐yl)methoxy)methyl)phenyl)octan‐3‐yl)benzyl)oxy)methyl)−1, 3‐phenylene)bis(9H‐carbazole)) (P(mCP‐Ox)‐I, ‐II, and ‐III)]. In addition, monomer 1 was copolymerized with styrene to produce copolymer P(mCP‐Ph) as a host material for bis[2‐(4, 6‐difluorophenyl)pyridinato‐C2, N](picolinato)iridium(III) (FIrpic), a blue‐emitting dopant. All mCP‐based copolymers displayed high glass transition temperatures (Tg) of up to 130–140 °C and triplet energies of up to 3.00 eV. The blue Ph‐PLEDs exhibited a maximum external quantum efficiency of 2.55%, in addition to a luminous efficiency of 8.75 cd A−1 when using the device configuration of indium tin oxide/poly(3, 4‐ethylenedioxythiophene):poly(styrene sulfonate)/P(mCP‐OX)‐III/P(mCP‐Ph):FIrpic(15 wt %)/3, 3′‐[5′‐[3‐(3‐pyridinyl)phenyl][1, 1′:3′, 1′′‐terphenyl]‐3, 3′′‐diyl]bispyridine/LiF/Al. The device bearing P(mCP‐Ox)‐III HTL, containing the highest composition of mCP unit, exhibited better performance than the other devices, which is attributed to induction of more balanced charge carriers and carrier recombination in the emissive layer. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 707–718